2014
DOI: 10.1007/s00213-014-3618-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of ten neuroactive steroids in plasma in Withdrawal Seizure-Prone and -Resistant mice during chronic ethanol withdrawal

Abstract: Rationale The rapid membrane actions of neuroactive steroids, particularly via an enhancement of γ-aminobutyric acidA receptors (GABAARs), participate in the regulation of central nervous system excitability. Prior evidence suggests an inverse relationship between endogenous GABAergic neuroactive steroid levels and behavioral changes in excitability during ethanol withdrawal. Objectives Previously, we found that ethanol withdrawal significantly decreased plasma allopregnanolone (ALLO) levels, a potent GABAer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 46 publications
2
33
2
Order By: Relevance
“…To provide direct support for the lack of involvement of neurosteroids in the antiseizure action of midazolam, plasma and brain levels of the neurosteroid allopregnanolone were determined by liquid chromatography-mass spectrometry in animals pretreated with midazolam. Allopregnanolone levels are commonly measured by mass spectrometry assay (Reddy et al, 2004;Porcu et al, 2009;Snelling et al, 2014). Allopregnanolone levels were determined 30 minutes after injection with an antiseizure dose of midazolam (1 mg/kg i.p.)…”
Section: Mechanisms Of Antiseizure Action Of Midazolammentioning
confidence: 99%
“…To provide direct support for the lack of involvement of neurosteroids in the antiseizure action of midazolam, plasma and brain levels of the neurosteroid allopregnanolone were determined by liquid chromatography-mass spectrometry in animals pretreated with midazolam. Allopregnanolone levels are commonly measured by mass spectrometry assay (Reddy et al, 2004;Porcu et al, 2009;Snelling et al, 2014). Allopregnanolone levels were determined 30 minutes after injection with an antiseizure dose of midazolam (1 mg/kg i.p.)…”
Section: Mechanisms Of Antiseizure Action Of Midazolammentioning
confidence: 99%
“…Endogenous neurosteroids that rapidly enhance γ-aminobutyric acid A receptor (GABA A R)-mediated inhibition (e.g., Belelli and Lambert, 2005; Carver and Reddy, 2013; Paul and Purdy, 1992) are formed by the 5α-/5β- and then 3α-reduction of the parent steroids progesterone, deoxycorticosterone (DOC), testosterone, and dehydroepiandrosterone (DHEA; e.g., Finn et al, 2004; Porcu et al, 2009, 2016; Snelling et al, 2014). The progesterone metabolites allopregnanolone (ALLO; 3α,5α-THP or tetrahydroprogesterone) and pregnanolone (3α,5β-THP) and the DOC metabolite tetrahydrodeoxycorticosterone (3α,5α-THDOC) are the three most potent neurosteroids characterized to date, as they enhance GABA A R-mediated inhibition with nanomolar (nM) potencies, directly activate GABA A Rs with micromolar potencies, and exert effects on other ligand gated ion channels with micromolar potencies (Belelli and Lambert, 2005; Belelli et al, 1990; Carver and Reddy, 2013; Paul and Purdy, 1992; Purdy et al, 1990; Rupprecht and Holsboer, 1999; Veleiro and Burton, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We and others found that WD is associated with a decrease in GABA A R inhibition mediated by a variety of factors that includes functional changes in GABA A R properties, a reduction in the steroidogenic effect of acute ethanol administration, and a decrease in endogenous ALLO levels (see Finn et al, 2004; Kumar et al, 2009). In rodents, monkeys, and humans, WD decreases ALLO levels in plasma and several brain regions (Beattie et al, 2017; Cagetti et al, 2004; Hill et al, 2005; Maldonado-Devincci et al, 2014; Romeo et al, 1996; Snelling et al, 2014; Tanchuck et al, 2009). In small cohorts of male and female alcoholics, the decrease in ALLO and 3α,5α-THDOC levels corresponded to an increase in the subjective ratings of anxiety and depression during days 4 – 5 of WD, versus controls (Hill et al, 2005; Romeo et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations